AIAA Atmospheric Flight Mechanics Conference 2011
DOI: 10.2514/6.2011-6459
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the Aeroelastic/Aeroservoelastic Interaction Using Adaptive Feedback Control Instead of Notching Filters

Abstract: This paper investigates the possibility that an adaptive feedback controller can be designed and implemented for the suppression of aircraft's structural vibration in the presence of any aeroelastic/aeroservoelastic interaction, instead of using the non-adaptive notching filters. Currently aircraft with non-adaptive control laws usually include roll-off or notch filters to avoid AE/ASE interactions. However, if changes in the aircraft configuration are significant, the frequencies of the flexible modes of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…The boundedness of r implies that α, α are bounded by virtue of the definitions of (18) and (19). Since the system is minimum phase and relative degree one, the boundedness of the output guarantees that any first order stable filtering of the input will remain bounded.…”
Section: Stability Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The boundedness of r implies that α, α are bounded by virtue of the definitions of (18) and (19). Since the system is minimum phase and relative degree one, the boundedness of the output guarantees that any first order stable filtering of the input will remain bounded.…”
Section: Stability Analysismentioning
confidence: 99%
“…A plethora of techniques is available for dealing with the effect of non-linear structural stiffness in the context of subsonic flow; linear control theory, feedback linearizing techniques, adaptive, and robust control techniques have been employed to account for these nonlinearities, e.g., [8]- [19]. Recently, neural-network-based (i.e., model-free) control approaches have been proposed in [20] and [21] to stabilize a nonlinear aeroelastic wing section.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers are seeking AFS solutions as an alternative to passive methods. 5 Maryland) in 2010 on the SensorCraft vehicle showed that a 25% total weight savings could be achieved by incorporating AFS into the controller. 7 Increasing flexibility in the structure of the wing may come with other consequences.…”
Section: Introductionmentioning
confidence: 98%
“…[10][11][12][13][14][15] The frequency of the modes are predicted either through computational methods or through experimental tests. A filter is then designed that reduces any energy from the controller commands within the spectrum of the notch.…”
Section: Introductionmentioning
confidence: 99%